PERLINDUNGAN HUKUM BAGI INVESTOR PEMILIK ASET KRIPTO DI INDONESIA - Muhammad Wimar (2023)
This study discusses the legal protection of investors for the loss of crypts shareholder assets. This research aims to explain how legal protection is for investors who own crypts assets in commodity futures exchanges in Indonesia and to find out whether the legal protection provided by PT. Indodax towards investors who own crypts assets with the legal system in Indonesia. The research questions that arise are how legal protection is for cryptocurrency investors if their assets are lost and what is the responsibility of PT.Indodax to crypt assets investors who experience loss of assets. Types of research conducted used in answering the problems in this study is a type of normative juridical research, while the problem approach used in this research is to use a theoretical approach. Sources of data in normative juridical research or normative legal research are only obtained from primary data sources and secondary data sources, which data obtained from literature related to the research object. Regulation of the Commodity Futures Trading Regulatory Agency Number 5 of 2019 concerning Technical Provisions for Organizing a Physical Crypt Asset Market, explains that the parties to this transaction are crypt assets traders and crypt assets customers. Crypt assets traders act as parties that facilitate crypt asset transactions between one customer and another. Article 22 of CoFTRA Regulation Number 5 of 2019 concerning Technical Provisions for Organising the Physical Crypto Asset Market on the Futures Exchange regulates dispute resolution in cryptocurrency asset transactions, and bitcoin buying and selling transactions facilitated by the Indodax website are also compliant with the principles of Indonesian contract law, which refers to the Indonesian Civil Code.